Parametric study on the effect of anchor’s geometry on the stress distribution and crack initiation direction in a concrete body (Fracture and Structural Integrity, 2025)
This work deals with investigations of the stress field distribution around a steel anchor embedded in a concrete. Tensile loading - pulling force of the steel anchor is considered, which is very often connected to concrete cone failure. Numerical simulations via finite element method were performed to obtain results for a large extent of geometrical configurations. In accordance with the basic idea of the maximum tangential stress criterion, the angle where this stress reaches its maximum was determined. The influence of selected geometrical parameters of the system on these angles was analyzed and it was found out that they can significantly affect the angle of the maximum tangential stress and consequently the shape of the cone failure. It was observed that the circumferential crack propagation is flatter with increasing length of the steel anchor’s embedment and with increasing anchor’s outer radius. The results obtained numerically agree sufficiently with experimental results especially when the crack direction is compared. Conclusions presented within this research are important for both design and assessment of anchor/concrete systems subjected to tensile loading.
Keywords: Steel anchors; Concrete cone failure; Finite element method; Maximum tangential stress; Critical distance